The lonD gene is homologous to the lon gene encoding an ATP-dependent protease and is essential for the development of Myxococcus xanthus. - Tojo, N (1993)
Myxococcus xanthus contains two genes (lonV and lonD) homologous to the Escherichia coli lon gene for an ATP-dependent protease. We found that the lonD gene encodes a 90-kDa protein consisting of 827 amino acid residues. The lonD gene product shows 49, 48, and 52% sequence identity to the products of the M. xanthus lonV, E. coli lon, and Bacillus brevis lon genes, respectively. When a lonD-lacZ fusion was used, lonD was expressed during both vegetative growth and development. However, while lonD-disrupted strains were able to grow normally vegetatively, the development of M. xanthus was found to be arrested at an early stage in these strains. The mutant strains were able to form neither fruiting bodies nor myxospores.